Ciprofloxacin stress changes key enzymes and intracellular metabolites of Lactobacillus plantarum DNZ-4 - Pin Chen; Xiaoqian Chen; Wei Yu; Bo Zhou; Lihua Liu; Yuzhuo Yang; Peng Du; Libo Liu; Chun Li (Food Science and Human Wellness)
Ciprofloxacin (CIP) is an antibiotic used to treat infections caused by bacteria. In this experiment, key enzymes and intracellular metabolites of Lactobacillus plantarum DNZ-4 was researched under CIP stress. The results showed that the activities of hexokinase, pyruvate kinase, β-galactosidase and Na+, K+-ATPase after 1/2 minimum bacteriostatic concentration (MIC) CIP treatment were significantly decreased (P < 0.01). Gas chromatography-mass spectrometry was used to analysis the changes of main metabolites in the cells and principal component analysis and partial least square model were constructed. The results indicated that CIP could cause changes in intracellular fatty acids, carbohydrates and amino acids, and the mechanism of amino acid metabolism under CIP stress was significantly inhibited. L. plantarum DNZ-4 made stress response to CIP by regulating the ratio of saturated fatty acids and unsaturated fats. This experiment revealed the changes of growth and metabolism mechanism of L. plantarum DNZ-4 under CIP stress, which help to provide technical means for the development of effective probiotics preparation products.